2007
DOI: 10.1002/j.2050-0416.2007.tb00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Beer Contain Compounds That Might Interfere with Cholesterol Metabolism?

Abstract: Elevated blood cholesterol is a problem for many people. Although a significant proportion of this cholesterol arises from metabolism within the body, approximately 50% comes from our diet. Certain plant sterols (phytosterols) are known to inhibit the absorption of this dietary cholesterol by the human body, and there are now several commercially available food products that contain these phytosterols. Barley malt, yeast and hops also contain phytosterols or similar materials that might potentially act as inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The only available data on plant sterols in beer are results from Muller et al (2007) and Rapota and Tyrsin (2015) [ 22 , 46 ]. Both indicated that BSS from malt and hop could compete with cholesterol for protein binding and uptake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only available data on plant sterols in beer are results from Muller et al (2007) and Rapota and Tyrsin (2015) [ 22 , 46 ]. Both indicated that BSS from malt and hop could compete with cholesterol for protein binding and uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Our own preliminary data showed that brewer’s hop and malting barley contain, respectively, >140 and >50 mg free plant sterols per 100 g DW [ 23 ]. Muller et al (2007) analyzed a few beer samples ( n = 4), proving the presence of BSS in beer, but the results were not quantitative [ 22 ]. Throughout the current study, BSSG, BSS, campesterol, ergosterol, and stigmasterol could be detected and quantified in a variety of different beers ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of fat-like substances on the formation of the colloidal system of beer is ambiguous and is caused by the nature of lipids. Complex lipid-like compounds’ phytosterols, which include β-sitosterol and homologues (stigmasterol, campesterol and brassicasterol) of barley and hops, as well as yeast ergosterol, are formed from lanosterol [ 135 , 136 ]. The biosynthesis of phytosterols has precursors in the form of acetic and mevalonic acids, which are converted in the process of fermentation to squalene with varying degrees of cyclization and conjugation [ 137 ].…”
Section: The Beer’s “Body” Biomoleculesmentioning
confidence: 99%
“…However, these applications are often focussed on developing methods to identify beer quality for comparison or quality control (Casey and Bamforth, 2010; Biancolillo et al , 2014; Giovenzana et al , 2014). Similarly, studies have also focussed on identifying differences between styles and beer components to quantify health concerns ranging from cardiomyopathy to cirrhosis and drinkability (Thomas and Millstone, 2003; Ogbonna, 2009) or benefits (Muller et al , 2007; Casey and Bamforth, 2010; Granato et al , 2010; Pihlava et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%